Notch receptor-ligand binding and activation: Insights from molecular studies - Chillakuri, C; Sheppard, D; Lea, S; Handford, P (2012)
The Notch receptor is part of a core signalling pathway which is highly conserved in all metazoan species. It is required for various cell fate decisions at multiple stages of development and in the adult organism, with dysregulation of the pathway associated with genetic and acquired diseases including cancer. Although cellular and in vivo studies have provided considerable insight into the downstream consequences of Notch signalling, relatively little is known about the molecular basis of the receptor/ligand interaction and initial stages of activation. Recent advances in structure determination of the extracellular regions of human Notch-1 and one of its ligands Jagged-1 have given new insights into docking events occurring at the cell surface which may facilitate the development of new highly specific therapies. We review the structural data available for receptor and ligands and identify the challenges ahead. © 2012 Elsevier Ltd.